Batteries: Nanoconfined LiBH4 as a Fast Lithium Ion Conductor (Adv. Funct. Mater. 2/2015). (January 2015) - Blanchard, Didier; Nale, Angeloclaudio; Sveinbjörnsson, Dadi; Eggenhuisen, Tamara M.; Verkuijlen, Margriet H. W.; Suwarno; Vegge, Tejs; Kentgens, Arno P. M.; de Jongh, Petra E.
<x xml:space="preserve">Abstract</x> A new type of electrolyte for all‐solid‐state batteries is presented by D. Blanchard, P. E. de Jongh, and team on page 184. Confining LiBH4 in the nanopores of a SiO2 scaffold leads to a room temperature conductivity of 0.1 mS cm−1, three orders of magnitude higher than for crystalline LiBH4. Lithium ions (blue spheres) move rapidly through LiBH4 near pore walls, while the core shows more conventional LiBH4 behavior, albeit with decreased phase transition temperatures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>